Association between Parenting Styles and Physical Growth among Toddlers - Maya Cobalt Angio Septianingtyas; Swanny Trikajanti Widyaatmadja; I’ien Noer’aini (GLOBAL HEALTH SCIENCE GROUP, 2026)
Early childhood represents a critical developmental stage in which family care and parenting play a fundamental role in shaping children’s health and growth outcomes. In coastal communities, socioeconomic challenges, limited parental supervision, and constrained educational access may influence parenting practices and, consequently, children’s physical growth. To identify the dominant parenting style among coastal families in Semarang City and analyse its association with toddlers’ physical growth. This quantitative cross-sectional study involved 371 families with toddlers aged 1–5 years living in North Semarang District, a coastal area of Semarang City. Samples were selected using stratified random sampling. Data were collected through a validated parenting style questionnaire based on Baumrind’s theory and anthropometric measurements following WHO Child Growth Standards. Data were analysed using descriptive statistics and the Chi-square test (p < 0.05). The permissive parenting style was the most dominant (49.9%), followed by authoritarian (27.5%) and authoritative/democratic (22.6%). Most toddlers (68.2%) showed normal growth, while 31.8% experienced problems such as underweight, stunting, or wasting. A significant association was found between parenting style and toddlers’ physical growth (χ² = 13.21; p = 0.001). Children raised with an authoritative (democratic) style had the highest proportion of normal growth (82.1%). Permissive parenting predominates among coastal families, reflecting socioeconomic constraints and limited parental involvement. Parenting style significantly affects child growth; thus, family-based interventions promoting structured and responsive parenting are essential to prevent growth problems in vulnerable coastal communities.